Beyond The Classroom: Where The Classroom Meets The Residence Halls Spring 2015 - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
What happens when you reenvision the traditional classroom concept? You get "Beyond the Classroom," a program which brings faculty and other campus leaders into the residential and scholarship halls to join students for dinner and present on a variety of topics. Typically, 2-3 events are planned for each semester, and it is a unique opportunity for students to learn more about the research that is being conducted by leaders across campus. This poster promotes the spring 2015 "Beyond The Classroom" events at Kansas State University: "Engineering a Green Future, One Change at a Time", "A Backstage Pass of How a University Runs: Candor, Confidence and a Candid Look at K-State", and "At war with the Buddha of Love: the Greatest Statue Not Yet Built".
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; Posters